Consensus Statement: Feature and Function Recommendations to Optimize Clinician Usability of Direct Interoperability to Enhance Patient Care - Lane, Steven R.; Miller, Holly; Ames, Elizabeth; Garber, Lawrence; Kibbe, David C.; Schneider, Joseph H.; Lehmann, Christoph U.; DirectTrust Clinicians' Steering Group (Applied Clinical Informatics, 2018)
Background Secure clinical messaging and document exchange utilizing the Direct Protocol (Direct interoperability) has been widely implemented in health information technology (HIT) applications including electronic health records (EHRs) and by health care providers and organizations in the United States. While Direct interoperability has allowed clinicians and institutions to satisfy regulatory requirements and has facilitated communication and electronic data exchange as patients transition across care environments, feature and function enhancements to HIT implementations of the Direct Protocol are required to optimize the use of this technology.Objective To describe and address this gap, we developed a prioritized list of recommended features and functions desired by clinicians to utilize Direct interoperability for improved quality, safety, and efficiency of patient care. This consensus statement is intended to inform policy makers and HIT vendors to encourage further development and implementation of system capabilities to improve clinical care.Methods An ad hoc group of interested clinicians came together under the auspices of DirectTrust to address challenges of usability and create a consensus recommendation. This group drafted a list of desired features and functions that was published online. Comments were solicited from interested parties including clinicians, EHR and other HIT vendors, and trade organizations. Resultant comments were collected, reviewed by the authors, and incorporated into the final recommendations.Results This consensus statement contains a list of 57 clinically desirable features and functions categorized and prioritized for support by policy makers, development by HIT vendors, and implementation and use by clinicians.Conclusion Fully featured, standardized implementation of Direct interoperability will allow clinicians to utilize Direct messaging more effectively as a component of HIT and EHR interoperability to improve care transitions and coordination.
Keywords: provider–provider communications; interfaces and usability; care transition; health information interoperability; health information exchange; user–computer interface; continuity of care document